Interpreting and Responding to Pandemics in Philosophical Traditions and Films of India - Jain, Pankaj (Worldviews, 2023)
India and the rest of the world continue to witness waves of COVID-19. In this article, I present myriad examples of ethical issues in the context of pandemics that hit India in the last few centuries. I also analyze the relevance of Indian texts and films in the context of various pandemics. The article quotes several primary and secondary texts to explore interpreting and responding to different pandemics and broader health issues. As the world reels under the COVID mayhem, it is time to take inspiration from various other medical professionals at the forefront of fighting this pandemic. We urgently need their compassion and not any recurrence of colonialism or racism that rears its head even today. Our collective responses to COVID-19 can prompt us to collectively mitigate and adapt to various climate changes across the planet by combining the ideas and imaginations from the “East” and “West.”